Marcellus of Ancyra and the lost years of the Arian controversy 325-345 - Parvis, Sara (Oxford University Press, 2006)
Is it true, as has often been claimed in recent years, that there was no real controversy in the period immediately following the Council of Nicaea? Sara Parvis argues not and she shows two opposing parties which had formed in support of Alexander of Alexandria and Arius in the years before Nicaea continued their activities